Characterization of Cebama low-pH reference concrete and assessment of its alteration with representative waters in radioactive waste repositories. (October 2020) - Vehmas, Tapio; Montoya, Vanessa; Alonso, Maria Cruz; Vašíček, Radek; Rastrick, Emily; Gaboreau, Stephane; Večerník, Petr; Leivo, Markku; Holt, Erika; Fink, Nicolas; Ait Mouheb, Naila; Svoboda, Jiří; et al.
Abstract: Concretes, mortars and grouts are used for structural and isolation purposes in radioactive and nuclear waste repositories. For example, concrete is used for deposition tunnel end plugs, engineered barriers, mortars for rock bolting and injection grouts for fissure sealing. Despite of the materials anticipated functionality, it is extremely important to understand the long-term material behaviour in repository environments. A reference concrete and mortar for the Cebama project based on a cement, silica and blast furnace slag ternary blend were designed and characterized in different laboratories with multiple experimental methods (XRD, XAS at the Fe and Cl K-edges, SEM-EDX, 29 Si and 27 Al MAS-NMR, TG-DSC, MIP and Kerosene porosimetry) and techniques (punch strength tests). The reference concrete enabled comparison of results from different institutes and experimental techniques, unifying the individual results to more comprehensive body. The Cebama reference concrete and mortar were designed to have high durability and compatible formulation with respect to an engineered barrier system in clay or crystalline host-rocks, having pore solution pH significantly lower than traditional concretes. This work presents main results regarding their characterization and alteration in contact with representative waters present in radioactive waste repositories. Pore solution pH of the matured reference concrete was 11.4–11.6. The main hydrated phases were C–S–H and C-A-S-H gels with a Ca:Si ratio between 0.5 and 0.7 and an Al:Si ratio of 0.05. Minor phases were ettringite and hydrotalcite. Iron(III) could be in the C–S–H phases and no Cl-bearing solid phases were identified. Connected porosity and pore size distribution was characterized by MIP observing that, as expected, the size of the pores in the hydrated cement phases varies from the micro-to the nanoscale. Connected porosity of both materials were low. Compressive strength of the concrete was 115 MPa, corresponding to traditional high-performance concrete. Degradation of these materials in contact with different waters mainly produce their decalcification and enrichment in Mg for waters containing high amount of this element, like the clay waters. Highlights: The performance of "low-pH" mix designs containing slag exceeds the performance of traditional Portland cement concretes. That slag is able to replace fly ash when producing "low-pH" mixtures, if needed due to material supply or quality problems. Eight experimental techniques have provided mechanical, hydraulic and geochemical properties of new designed materials. Micro-mortar in contact with clay and bentonite waters, shows a Mg enrichment and calcium depletion at the reaction front.